Le jeu de scène: traductions et traducteurs à travers les cultures et les genres littéraires - Mihalache, Iulia (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article aims at revealing a series of collective and individual represen-tations of translation and of the translating subject present in the work of fiction. The authors chosen for this analysis belong to a multicultural space and are therefore inclined to reflect upon translation. Every author will opt for a specific genre. However , are there any recurrent representations of translation and of the translating subject from one genre to the other, across the cultures and across the different writing styles? In order to analyse the transfer of representations between these genres, but also between translation theory and fiction, we have selected the following texts: Carlos Batista ’s Bréviaire d’un traducteur (2003), Ólafur Jóhann Ólafsson ’s Absolution (1994), Dezsó Kosztolányi’s Le Traducteur cleptomane (1985), José Carlos Somoza’s La caverne des idées (2002), Michel Orcel’s Les larmes du tra-ducteur (2001) and John Crowley ’s The Translator (2002).